The Christianization of Scandinavia in the Viking Era : Religious Change in Adam of Bremen's Historical Work. - Grzybowski, Lukas G. (Beyond Medieval Europe, 2021)
This book discusses Adam of Bremen's perceptions and interpretation of the Christianization of Scandinavia in the Early Middle Ages. The views the chronicler presents in the Gesta Hammaburgensis constitute the central element of this analysis. By departing from the historiography--both the older view of the Gesta as trustworthy, and the recent view of the work as unreliable and biased--this book focuses instead on the Christianization of Scandinavia as an authorial concept. What follows is a reevaluation of the Gesta's significance both to its medieval audience and the modern historian.